Manajemen Pengelolaan Dana Zakat pada Yayasan Rumah Santunan Raudhah di Jorong Tiga Batur Nagari Sungai Tarab Kecamatan Sungai Tarab Kabupaten Tanah Datar - Rohdatul Aisy (ZAWA: Management of Zakat and Waqf Journal, 2024)
The problem discussed in this research is that there are still many people who have not received the benefits of zakat infaq alms, even though these people are already classified as people who are entitled to receive zakat. Meanwhile, in its implementation, there are several people who are classified as well off but receive benefits from raudhah compensation. Furthermore, in its implementation, people who receive this compensation have the status of orphans and still receive compensation, while orphans are not included in the group of zakat recipients. Apart from that, this zakat recipient is not entitled to receive it because he is classified as well-off, this is because the parents of the zakat recipient own a business and have quite a lot of rice fields so this recipient is not entitled to receive zakat because he is a well-off person. This type of research is field research using descriptive qualitative methods. The data collection techniques that the author uses are observation, interviews and documentation. The data analysis technique that the author uses is data reduction, data presentation and drawing conclusions. Based on the research results, it can be concluded that the management of zakat funds at the raudhah charity house foundation consists of collecting zakat funds and distributing zakat funds. Zakat funds are collected using two methods, namely the direct method and the indirect method. Where muzakki can deliver zakat directly to the administrators of the raudhah charity house foundation. Indirect collection can be done by sending zakat by muzakki via transfer via the account number of the raudhah compensation house. Distribution of Zakat Funds, distribution of funds is the activity of distributing a number of assets that have been collected by the LAZIS institution from muzakki to be distributed to mustahik (people who are entitled to receive them).